2008
DOI: 10.1002/ca.20726
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic activity and thickness of masticatory muscles in children with unilateral posterior crossbite

Abstract: The aim of this study was to assess the electromyographic (EMG) activity and thickness of the masseter and anterior temporalis muscles in children with unilateral posterior crossbite (PCB). Thirty-six children (22 boys, 14 girls, and mean age of 8.8 +/- 1.1 years) were divided into the following groups: The case group with 20 PCB patients (10 on the left side, 10 on the right side); the control group with 16 normal occlusion (NOccl) subjects. EMG activity was recorded with bipolar surface electrodes at rest an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2010
2010
2045
2045

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 37 publications
2
34
0
2
Order By: Relevance
“…It has also been suggested that ultrasound parameters may characterize muscular pain, injury and dysfunction [48][49][50][51][52]. Moreover, ultrasonography has been used along with EMG to provide more comprehensive information about the activities and properties of skeletal muscles [53][54][55][56][57]. We have recently proposed using the real-time muscle morphological change detected by ultrasound, namely sonomyography (SMG), for the prosthetic control [58,59] and for assessment of isometric muscle contraction [60][61][62] and isotonic contraction [63,64].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that ultrasound parameters may characterize muscular pain, injury and dysfunction [48][49][50][51][52]. Moreover, ultrasonography has been used along with EMG to provide more comprehensive information about the activities and properties of skeletal muscles [53][54][55][56][57]. We have recently proposed using the real-time muscle morphological change detected by ultrasound, namely sonomyography (SMG), for the prosthetic control [58,59] and for assessment of isometric muscle contraction [60][61][62] and isotonic contraction [63,64].…”
Section: Introductionmentioning
confidence: 99%
“…During marking and palpation, the soft tissue may undergo slight displacement, in the order of a few millimeters, depending on the direction of finger pressure applied to the skin. The use of palpation during muscle contraction (Arat et al, 2008), zygomatic arch (Andrade et al, 2009) and gonial angle have already been referred by other studies (Andrade et al, 2009;Garcia-Morales et al, 2003;Leung and Hägg, 2001), however, in less detail than the exposed in this manuscript. The scalp boundary limits the placement of surface electrodes over AT muscle, as reported in previous studies (Andrade et al, 2009).…”
Section: Discussionmentioning
confidence: 78%
“…Muscle dimension determination by ultrasonography has been used as a parameter of muscle form and function in many studies [9][10][11]14,15 , and, interestingly, facial features are usually studied in profile. In this study, the relationship between hard and soft tissue cephalometric variables was investigated and correlated with the orbicular oris thickness at rest and in the contracted state in subjects with Class I and Class II malocclusion.…”
Section: Discussionmentioning
confidence: 99%